(untitled) - Fenster, Eugene J. (Menlo Park, California, 1997)
The Biology: Concepts and connections, 2nd edition, each chapter consists of a series of concept modules, each taking up no more than two facing pages. The overall organization of the text is based on the interdisciplinary approaches, and biological science as a process.
Keywords: Biology,Life sciences,Natural history,Lịch sử tự nhiên,Sinh học,Khoa học đời sống